Empreendedorismo rural como mecanismo de desenvolvimento: limites à realidade da agricultura familiar em Sergipe - Vasconcelos, Ramon Oliveira (2019)
The study on the issue of entrepreneurship in the rural area of Sergipe aims to address the rebounding constraints on family farming that they adopted from innovation processes, technology absorption, property management, forming productive chains, creates marketing mechanisms that contribute to increase and diversify production and thereby intensify household incomes. The general objective of this study is based on the analysis of the relevant elements of family farming in Sergipe's rural space from the perspective of rural entrepreneurship in articulation (or not) with public policies in the rural environment, given the importance of the impacts on the rural development of the micro-regions of Itabaiana and Carira. This is justified by several variables that indicate and characterize the performance of rural producers that goes beyond the traditional conception of family farming. Work conducted with field research among entrepreneurial actors, of qualitative nature, taking into consideration the relevance of the empirical and inductive approach. The rural entrepreneur sets goals, has planning, market vision seeks constant training, is involved with the local community, has environmental concerns and actions. A self-critical analysis of the limits of entrepreneurship as a social and economic process is necessary, as well as its ideological aspect, which impacts on the formation of a generation of individualist actors. Therefore, family farming in the region under study is being worked on in the transformation cycle expressed by the system of production and application of entrepreneurship. This demonstrates that a new pattern of production has increased incomes, thereby improving the living conditions of the farmer and family as a particular management mechanism in line with entrepreneurial efficiency.